Hydraulic jump over sloping rough floors. Issue 2 (3rd May 2016) - Kumar, Mohit; Lodhi, A.S.
Abstract : This study presents the result of a series of experiments conducted to study the impact of channel slopes, along with channel bed roughness, on characteristics of a hydraulic jump. For this study, three slopes of a flume, viz. 0.000463, 0.00986 and 0.01552, and five bed roughness heights, i.e. 0.002, 0.00398, 0.0056, 0.007 and 0.011 m have been used. The analysis of the data revealed that there was no significant impact of bed roughness heights on characteristics of a hydraulic jump in sloping channels. However, the channel slope significantly affected its characteristics. The existing relationship to estimate the sequent depth ratio in sloping channels was considered for its applicability and it was found unsatisfactory. Therefore, a new relationship is proposed for the same. The comparison between the observed values for the sequent depth ratio, length of a roller and relative energy loss showed an agreement with the calculated values obtained from the proposed relationships.